Development of an Acid-Base E-Module Based on Guided Discovery Learning with Ethnoscience Content to Improve Literacy and Numeracy - Nadia Marsila; Yerimadesi; Alizar; Andromeda (Postgraduate, University of Mataram, 2025)
This research aims to develop a chemistry learning e-module for acids and bases based on guided discovery learning, incorporating elements of ethnoscience to improve students' literacy and numeracy. The guided discovery learning approach was chosen to encourage students to actively construct knowledge through guidance, while the integration of ethnoscience aims to link chemistry concepts with local wisdom to increase student relevance and understanding. The research method used was Research and Development (R&D) with the 4D development model (Define, Design, Develop, Disseminate). The research instruments included an expert validation sheet, a student response questionnaire, and literacy and numeracy tests. The validation results indicated that the e-module was highly feasible in terms of content, presentation, and language. A limited trial demonstrated significant improvements in students' literacy and numeracy skills after using the e-module. Therefore, this e-module is effective as an alternative learning medium for contextual and meaningful chemistry learning.